Implikasi Etika dan Hukum dalam Penggunaan Teknologi Pengenalan Wajah: Perlindungan Privasi Versus Keamanan Publik - Rambe, Rahmat; Abdurrahman, Lukman (Jurnal Hukum Caraka Justitia, 2024)
Facial recognition technology has been widely applied in everyday life and raises pros and cons, especially in the legal and ethical realms related to protecting privacy and public security. This research investigates the moral and legal implications of implementing this technology, with a focus on the conflict between individual privacy and public safety. Through a comprehensive literature review, this research analyzes various relevant views and findings. Researchers’ conclusions often highlight the dilemma between ethics and law in the use of facial recognition technology, emphasizing the importance of striking a balance between protecting privacy and public safety. This research aims to make a significant contribution to understanding this debate and promoting responsive and fair policy.